KONFLIK ISRAEL - PALESTIN DARI ASPEK SEJARAH MODEN DAN LANGKAH PEMBEBASAN DARI CENGKAMAN ZIONIS - Mohd Nor, Mohd Roslan (Journal of Al-Tamaddun, 2010)
President of the United States, Obama, speaking in Cairo in June 2009, expressed deep sympathy to the Palestinians who have been oppressed for over a century. Zionist occupation of Palestine has changed the landscape of government in the Middle East. Some of the scholars believe that as long as the injustice committed by the Zionists, so long that there can be no peace in the region in particular and the world in general. This article is to review aspects of the modern history of the conflict and suggests some steps that can be brought to the goodness and global peace.